2008
DOI: 10.1155/2008/131702
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence Study of Europium (III) Complex with Coumarin3‐Carboxylic Acid

Abstract: The europium (III) complex of coumarin-3-carboxylic acid (C3CA) has been prepared and characterized on the basis of elemental analysis, IR, and emission (photoluminescence and electrochemiluminescence) spectroscopy. The synthesised complex having a formula Eu(C3CA) 2 (NO 3 )(H 2 O) 2 was photophysically characterized in solution and in the solid state. Electrochemiluminescence, ECL, of the system containing the Eu(III)/C3CA complex was studied using an oxide-covered aluminium electrode. The goal of these studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Their complexation ability in respect to different metal ions has been studied and discussed widely in a considerable number of investigations [5][6][7][8][9]. It has been found that the binding of a metal to the coumarin moiety retains or even enhances its biological activity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Their complexation ability in respect to different metal ions has been studied and discussed widely in a considerable number of investigations [5][6][7][8][9]. It has been found that the binding of a metal to the coumarin moiety retains or even enhances its biological activity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many others metal complexes were also studied as ECL luminophores [21]. These central metal ions include Os(II) [39], Tb(III) [41][42], Eu(III) [43][44], Pt(II) [44], Mo, or their combinations such as Os(II)-Ru(II) and Os(II)-Ir(III) [21]. However, Ru and Ir are the most frequently used because they have the highest ECL emission efficiency, while others have lower efficiencies.…”
Section: Other Metal Complexesmentioning
confidence: 99%
“…The research reveals that the photophysical and electrochemical properties (photoluminescence quantum yield, electrochemical stability, and ECL efficiency) are strongly dependent on the donors and acceptors as well as the nanoparticle size and shape. , Coumarin and its derivatives are of great interest as good electron acceptors in biological and medical applications due to their good biological activity as well as in OLEDs because of its high photoluminescence quantum yields . Some ECL emitters of coumarin derivatives have been reported, including coumarin 30, arylamino-substituted coumarin, donor-substituted phenylethynylcoumarins, three different coumarin derivatives, europium­(III) complex with coumarin 3-carboxylic acid, and N -coumarin derivatives . Despite the remarkable properties and uses of coumarin derivatives, to the best of our knowledge, there is no report on the ECL of organic nanoparticles made from coumarin derivatives in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%